Long-term benefits of EPs® 7630 in patients with acute sinusitis: a real-world cohort study - Tisch, Matthias; Roháč, Lubomír; Reineke, Thorsten; Burkart, Martin; Kostev, Karel (Frontiers in Pharmacology, 2024)
Background: We evaluated whether EPs ® 7630 prescription in patients with acute sinusitis (AS) is associated with less frequent recurrence of AS, occurrence of chronic sinusitis or nasal polyps, or fewer antibiotic prescriptions.Methods: This retrospective cohort study used electronic medical records from the IQVIA Disease Analyzer database. Associations between initial therapy (EPs ® 7630, antibiotics, intranasal corticosteroid (INCS), or corticosteroid-free nasal spray within three days of AS diagnosis) and AS recurrence, incidence of chronic sinusitis or nasal polyps or rate of antibiotic prescription were studied using multivariable Cox or logistic regression models, adjusting for sex, age, insurance status, month of diagnosis, and comorbidity.Results: A total of 216,360 patients were analyzed. INCS prescription was associated with a higher risk of recurrent AS (HR:1.40; 95% CI:1.01-1.92) and a higher incidence of chronic sinusitis or nasal polyp diagnosis (HR:1.39; 95% CI:1.01-1.92) compared to EPs ® 7630. Initial antibiotic therapy was significantly associated with higher risk of new antibiotic prescription in the period of 31-365 days after the index date compared to EPs ® 7630 (OR:2.20; 95% CI:1.66-2.92).Conclusion: EPs ® 7630 prescription is associated with long-term benefits in AS patients. EPs ® 7630 can help to reduce inappropriate antibiotic use and might reduce the risk of chronic sinusitis or nasal polyps.